2017
DOI: 10.5812/ijvlms.11158
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Factors Affecting the Acceptance of E-learning in Higher Education

Abstract: Background: As the main step to implement and develop electronic learning (e-learning), it is very important to understand how learners accept it. The current study aimed at examining the main factors of e-learning acceptance by the students of Garmsar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
(27 reference statements)
5
21
0
Order By: Relevance
“…It has been shown in numerous studies conducted earlier that social influence (SI) has a significant association with PU [7], [40]- [42]. Furthermore, social influence (SI) can have a stronger impact on perceived ease of use (PEOU) of elearning [7], [34]. Hence, the following hypotheses are suggested:…”
Section: Social Influence (Si)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in numerous studies conducted earlier that social influence (SI) has a significant association with PU [7], [40]- [42]. Furthermore, social influence (SI) can have a stronger impact on perceived ease of use (PEOU) of elearning [7], [34]. Hence, the following hypotheses are suggested:…”
Section: Social Influence (Si)mentioning
confidence: 99%
“…The significant influence of perceived ease of use (PEOU) on perceived usefulness (PU) is shown in a previous research. In the past, several studies were carried out, which showed that there is a positive correlation between the perceived ease of use (PEOU) and the behavioral intention to use E-learning (BI), and this relationship is direct as well as indirect [1], [7], [17], [18], [27], [32], [34], [43], [46], [56], [58]- [61]. Moreover, there is strong empirical support for the correlation between PU and the attitude towards the use in the previous studies [17], [24], [32], [40], [43], [56], [62]- [67].…”
Section: 7mentioning
confidence: 99%
“…Previous studies found that SQ has a positive impact on perceived ease of use of e-learning [26], [32]- [34]. Besides, it was also found that SQ has a positive effect on perceived usefulness of e-learning [29], [33], [35]. Therefore, the following hypotheses were formulated:…”
Section: ) System Quality (Sq)mentioning
confidence: 99%
“…The e-learning system can only be accepted by the students when they perceive that its use is going to improve their learning performance. Previous e-learning studies indicated that there is a significant positive correlation between perceived usefulness (PU) and the behavioral intention to use the e-learning system (BI) [29], [80], [81]. Hence, the following hypothesis is formulated: H11: Perceived usefulness (PU) has a positive effect on the behavioral intention to use (BI) the e-learning system.…”
Section: ) Perceived Usefulness (Pu)mentioning
confidence: 99%
“…In TAM 3, Venkatesh & Bala (2008) find that perceived usefulness was the strongest predictor of behavioral intention at all time periods. Later on, some studies on e-learning in higher education imply a constructive relation between PU and the BI Hsia et al, 2014;Mahmodi, 2017).…”
Section: Perceived Usefulnessmentioning
confidence: 99%